Evolution of Energy and Exergy Efficiency in the European Road Freight Industry, 1978–2018 - Martulli, Alessandro; Galvin, Ray; Ruzzenenti, Franco (Frontiers in Energy Research, 2021)
In the last four decades the European truck industry has made remarkable progresses in energy efficiency, but this higher efficiency has failed to materialize in lower consumption per unit of load and distance (Tkm). One possible explanation is rebound effects due to average travelling speed and power enhancements. We present here an original set of data covering forty years of truck tests of 526 commercial vehicles and 28 different European brands, showing that energy efficiency (fuel economy) of heavy-duty trucks improved by 43% and (engine) power by 44%. We propose exergy as a metric to capture both dimensions and estimate that exergy efficiency increased by 73% over the same period, with an estimated speed rebound effect generally positive among the trucks tested on road conditions. Rebound effects caused by increased speed add to other sources of rebound like load, distance and frequency of journeys to potentially undermine gains delivered by higher energy efficiency. Our results provide evidence of the existence in the transport sector of a trade-off between power and efficiency as theoretically described by finite-time thermodynamics.